Analysis of different therapeutic schemes combining cyclophosphamide and doublestranded DNA preparation for eradication of Krebs-2 primary ascites in mice - E. A. Potter; E. V. Dolgova; A. M. Minkevich; V. P. Nikolin; N. A. Popova; Ya. R. Efremov; S. I. Baiborodin; V. A. Rogachev; A. S. Proskurina; A. V. Kozel; O. S. Taranov; V. V. Omigov; et al. (Вавиловский журнал генетики и селекции)
In the present paper, we report on the series of experiments where multiple regimens of CP and dsDNA injections were tested for targeting the ascites form of murine Krebs-2 cancer in situ. We show that combining CP with cross-linked human and salmon dsDNA results in a synergistic toxicity for ascites-bearing mice, an observation supported by the histopathology analysis of organs and tissues of experimental animals. In contrast, using a composite mixture of native and cross-linked human and salmon DNA after CP injections leads to a significant increase in average lifespan of the treated mice. Further, we demonstrate that repeated rounds of CP+dsDNA injections result in dramatic anticancer effect. The timing of injections is chosen so that they target the cells that were insensitive to the previous treatments as they were in the G2/M phase. 3-4 rounds of injections are needed to eliminate the subpopulation of tumor-initiating cancer stem cells. Our experiments identified the regimen when complete resorption of the primary Krebs-2 ascites occurs in all of the treated animals, followed by a remarkable remission period lasting 7-9 days. Yet, this regimen does not prevent secondary site metastases (either solid or ascites form) from developing, which is likely caused by the migration of ascites cells into adjacent tissues or by incomplete eradication of cancer stem cells. To address these and other questions, we expanded the study and performed histopathology analysis, which indicated that secondary metastases is not the only cause of death. In fact, many animals displayed unfolding systemic inflammatory reaction which was culminated by multiple organ failure. Thus, we developed the concept for treating ascites form of Krebs-2 cancer, which allows elimination of the primary ascites.